Synthesizing Cash for Clunkers: Stabilizing the Car Market, Hurting the Environment - Stefan Klößner; Gregor Pfeifer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We examine the impact of European car scrappage programs on new vehicle registrations and respective CO2 emissions. To construct proper counterfactuals, we develop MSCM-T, the multivariate synthetic control method using time series of economic predictors. Applying MSCM-T to a rich data set covering two outcomes of interest, ten economic predictors, and 23 countries, we first analyze Germany which implemented the largest program. We find that the German subsidy had an immensely positive effect of 1.3 million program-induced new car registrations. Disentangling this effect reveals that almost one million purchases were not pulled forward from future periods, worth more than three times the program's 5 billion budget. However, stabilizing the car market came at the cost of 2.4 million tons of additional CO2 emissions. For other European countries with comparable car retirement schemes, we show further positive results regarding vehicle registrations. Finally, we demonstrate that all non-scrapping countries could have considerably backed their vehicle markets by adopting scrappage subsidies.
Keywords: D04; D12; H23; 330